Multi-rigid-body dynamics and online model predictive control for transformable multi-links aerial robot*. (2nd October 2019) - Shi, Fan; Zhao, Moju; Anzai, Tomoki; Ito, Keita; Chen, Xiangyu; Nozawa, Shunichi; Okada, Kei; Inaba, Masayuki
Abstract : Transformable multi-links aerial robots have great potentials in application relying on the transformable features to change its shape during the flight. Compared to traditional quadrotor robots, transformable multi-links robots are equipped with servo motor between links. To simplify the non-linear dynamic system, the previous work restricts the robot to transform in very slow speed so that the robot could be approximated as a quadrotor robot at each time point. However, tradeoff comes as the dynamic performance is given up. In this paper, we come up with a new framework combining of computationally efficient non-linear model predictive controller and motion primitive to optimize thrust force and joints trajectory of the multi-links aerial robot. Finally, we verify our framework with fast transformation motions and table tennis task which requires dynamic performance. GRAPHICAL ABSTRACT: